Mindful Communication Dalam Layanan Bimbingan Kelompok Untuk Mengurangi Perilaku Phubbing Pada Remaja: Sebuah Kajian Literatur - Risa Agustin; Akhmad Fajar Prasetya (CV. SINAR HOWUHOWU, 2025)
The phenomenon of phubbing has increasingly emerged among adolescents along with the rapid growth of smartphone use. Previous studies indicate that this behavior negatively affects social interaction quality, empathy, academic attention, and students’ psychological well-being. This article reviews national and international research on phubbing and examines the effectiveness of group guidance interventions that integrate mindful communication and mindfulness-based counseling techniques. The review shows that mindful communication enhances presence, self-regulation, empathy, and attentiveness, making it a relevant approach for reducing phubbing behavior. The findings further highlight that developing a group guidance model grounded in mindful communication has strong potential as an innovative comprehensive school counseling service to address phubbing among students.